Micro/nanoarrays and their applications in flexible sensors: A review. (August 2022) - Lin, J.X.; Hu, H.W.; Luo, J.; Miao, L.; Yang, Z.H.; Chen, M.; Zhang, M.; Ou, J.Z.
Abstract: Flexible sensors are considered the key components of human wearable point-of-care (POT) devices. There have been enormous efforts devoted to improving the sensing performances and the degrees of comfortableness of flexible sensors in response to the rapid demands for accurate patient monitoring in healthcare settings. The implementation of two-dimensional (2D) or three-dimensional (3D) micro/nanoarrays with periodic and aligned structures on the sensitive nanoscale materials of flexible sensors is recognized as one of the most effective and viable approaches to enhance the sensing properties. In this review, we firstly perform a comparative study on the fabrication methods of 2D and 3D micro/nanoarrays. Meanwhile, the applications of micro/nanoarrays in various flexible sensors for detecting strain, pressure, temperature, gas, and so forth are summarized, while the correlations between the sensing performances and the fabrication approaches are critically discussed. This review may provide insightful guidance for realizing flexible sensors with ultra-high sensitivity in a wide range of applications.